Weiterbildung an Hochschulen Der Beitrag der DGWF zur Förderung wissenschaftlicher Weiterbildung - Hörr, Beate; Jütte, Wolfgang (W. Bertelsmann Verlag, 2017)
The anthology offers an examination of the structures, functions and operations of the German Association for University Continuing and Distance Education (Deutsche Gesellschaft für Wissenschaftliche Weiterbildung und Fernstudium e.V. - DGWF). The papers analyse the history of this expert association as well as the thematic priorities of the twelve sections (four work groups and eight national groups). The volume is complemented by an overview of cross-border activities and influential articles on the current status of scientific further education at universities, which is actually a relatively young academic discipline.